OPTIMALISASI BIAYA TRANSPORTASI UNTUK PENDISTRIBUSIAN ROTI MENGUNAKAN METODE VOGEL APROXIMATION (STUDY KASUS: PT ROTPAK) - Jeniver F Sirami; Ida Margareta Resiwangge, Herlina Lenora Yowei, Heru Sutejo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Efficient distribution is a key component in modern logistics systems, especially in food industries such as bread factories. This study examines the application of Vogel's Approximation method in the optimisation process of bread distribution from PT RotPak, located in Waena, to a number of demand points. This method was chosen for its ability to produce efficient initial solutions that are close to the optimum. The calculation results show that the total distribution cost can be minimised to 510 cost units. This study contributes to data-driven distribution decision-making and heuristic methods in small and medium-sized industrial environments.